Enhancing the Capacity of Large LEO Satellites with Internetworked Small Piggybacks for Low Latency Payload Data Transmission - Ramalakshmi, V; Madhavareddy, Venkata Narayana; Immadi, Govardhani; Srinivasan, V. V. (Engineering, Technology & Applied Science Research, 2024)
In most cases, the utilization of the costly payload onboard Low Earth Orbit (LEO) satellites is restricted by the limited throughput of the payload data downlink to the ground station during the visibility window. The usefulness of these data in critical applications reduces due to the large latency of the process. Different techniques involving efficient modulation schemes, increased power within the allowed level and frequency band, and capacity enhancement using close-by satellites have been studied and implemented with their relative merits and limitations in an attempt to reduce the latency of the data to the user. The present study proposes a constellation of low-cost data relay satellites placed in the same orbital plane along with the main satellite, increasing directly the effective visibility window. As a result, the utility of the main satellite is also increased by the same factor. A detailed analysis of the constellation and configuration of the relay satellites is presented in this paper.